PERANAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. KALIMANTAN PRIMA PERSADA TERHADAP PENINGKATAN PENDAPATAN DAN PENDIDIKAN MASYARAKAT KECAMATAN LOKPAIKAT KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - Teguh Agung Samudra; Idiannor Mahyudin; Gunawansyah Gunawansyah; Susilawati Susilawati (Universitas Lambung Mangkurat, 2015)
Corporate Social Responsibility (CSR) is an idea that corporate social responsibility was born to answer the problem posed in the midst of society. CSR is expected to help the development process by increasing the role of the company for the welfare of the community, especially communities around the company. The purpose of this study is to get the concept CSR program of PT. Kalimantan Prima Persada (PT KPP) in accordance with the needs of the community, social public opinion regarding the company's existence and analyze the relationship between CSR programs to increase revenue and public education. The research was carried out by simple random sampling with the number of respondents 60 families (family head). Respondents are the beneficiaries of CSR in 3 (three) villages, namely Binderang, Bitahan Baru and Bitahan. Analysis of the data with the three stages, namely to determine the public perception was measured using a Likert scale (Allen and Seaman, 2007) and categorized into three major groups, namely good, average, and bad. Analyzed for levels of perception using calculating Value Perception (NP), the classification category is based on the total score obtained by the respondents for each aspect presented on the questionnaire. For data analysis the factors that influence the perception of the community in the role of CSR PT. KPP using multiple regression analysis (Multiple Linear Regression Analysis) processed through the SPSS program (Statistical Program for Social Science). The results showed that the concept of CSR Program PT. KPP has had planning documents and strategies in the CSR Program SOP system so that programs that have been implemented with the aim to empower people and can fit the needs of the community. As many as 15% of respondents admitted that the existence of a company's CSR program is quite good and affect the existence of the company, while the respondents who perception bad as many as 10%. Income and household education in the community has increased significantly when compared between before the CSR program (in 2007) and after the CSR program (in 2012).